The protolytic properties of the sialorphin derivative Pal-Lys-Lys-Gln-His-Asn-Pro-Arg in an aqueous solution - Marek Pająk; Elżbieta Kamysz; Jakub Fichna; Magdalena Woźniczka (Polskie Towarzystwo Farmaceutyczne, 2023)
The present work describes the protolytic properties of the sialorphin derivative (Pal-Lys- Lys-Gln-His-Asn-Pro-Arg) in an aqueous solution, at constant temperature 25.0 ± 0.1 °C and ionic strength 0.1 M (NaClO4), over the entire pH range. The overall protonation constants of the studied ligand were calculated by the potentiometric method. The logarithm values of the stepwise dissociation constants of the sialorphin derivative were found to be: [LH] = 11.88 ± 0.09, [LH2]+ = 9.96 ± 0.03, [LH3]2+ = 8.71 ± 0.03, [LH4]3+ = 5.49 ± 0.03, [LH5]4+ = 2.82 ± 0.03. The percentage of each species formed in an aqueous solution was estimated from the species distribution curves as a function of pH (82% [LH] at pH 11.0, 68% [LH2]+ at pH 9.3, 95% [LH3]2+ at pH 7.1, 90% [LH4]3+ at pH 4.2, 85% [LH5]4+ at pH  2.0). The five protonation constants indicate that the studied ligand can be very active in forming complexes with different metal ions. In addition, the sialorphin derivative can also be tested as a bioactive material, which warrants its further in vitro and in vivo studies.